Brief Report: Programmatic Scale-up of Tuberculosis Preventive Treatment Among People Living With HIV Through Targeted Technical Assistance to High-Volume Antiretroviral Treatment Sites—Nigeria, 2018–2019. (1st December 2020) - Boyd, Andrew T.; Odume, Bethrand; Sidibe, Kassim; Onotu, Dennis; Ogbanufe, Obinna; Mgbakor, Ifunanya; Swaminathan, Mahesh
Abstract : Background: Tuberculosis preventive treatment (TPT) is a critical intervention to reduce tuberculosis mortality among people living with HIV (PLHIV). To facilitate scale-up of TPT among PLHIV, the Nigeria Ministry of Health and the US Centers for Disease Control and Prevention (CDC) Nigeria, supported by US President's Emergency Plan for AIDS Relief implementing partners, launched a TPT-focused technical assistance strategy in high-volume antiretroviral treatment (ART) sites during 2018. Setting: Nigeria has an estimated 1.9 million PLHIV, representing the second largest national burden of PLHIV in the world, and an estimated 53% of PLHIV are on ART. Methods: In 50 high-volume ART sites, we assessed readiness for TPT scale-up through use of a standardized tool across the following 5 areas: clinical training, community education, patient management, commodities and logistics management, and recording and reporting. We deployed a site-level continuous quality improvement strategy to facilitate TPT scale-up. Implementing partners rapidly disseminated best practices from these sites to across all CDC-supported sites and reported aggregate data on monthly TPT initiations. Results: Through this targeted assistance and rapid dissemination of best practices to all other sites, the number of PLHIV who initiated TPT across all CDC-supported sites increased from 6622 in May 2018, when the approach was implemented, to 48, 661 in September 2018. Gains in monthly TPT initiations were sustained through March 2019. Conclusions: Use of a standardized tool for assessing readiness for TPT scale-up provided a "checklist" of potential barriers to TPT scale-up to address at each site. The quality improvement approach allowed each site to design a specific plan to achieve desired TPT scale-up, and best practices were implemented concurrently at other, smaller sites. The approach could assist scale-up of TPT among PLHIV in other countries.